Gender difference and scientific literacy level of secondary student: a study on global warming theme. Issue 2 (February 2019) - Hardinata, A; Putri, R E; Permanasari, A
Abstract: A study was conducted to measure scientific literacy of lower secondary students in the learning theme of global warming. This survey research involved 112 fifteen-year students who attend the science course at three secondary schools in Bandung. Sampling was done by random sampling method. The scientific literacy of students was measured by using a developed test of science literacy. The test was constructed under PISA framework 2015 and validly used to measure scientific literacy between high and low-achieving students. The finding showed that no significant differences among three competencies of scientific literacy. The average score of each competency was in moderate category. It also revealed that there is no significantly different between male and female students.